Isokinetic strength and sprint times in english premier league football players - Cotte, T.; Chatard, J. C. (Biology of Sport, 2011)
This study assessed the relationship between isokinetic leg strength and 10 to 30-m sprint times in 14 professional English Premier League football players: 6 international and 8 non-international. Isokinetic measurements were performed at 60, 180, 240 and 300°/s on knee extensors and flexors. International players were shorter (179 ± 7 cm versus 185 ± 2.5 cm, P < 0.01), lighter (78.6 ± 4.8 kg versus 88.8 ± 6 kg, P < 0.01) and leaner (11.4 ± 1% versus 14.3 ± 2.2%, P < 0.02) than the non-international players. In absolute values, extensor peak torques (PT) were significantly lower for the international players than for the non-international players at 60, 180, 240 and 300°/s while flexor PT were significantly lower only at 180, 240 and 300°/s. These differences were explained by body weight variations. Indeed, when expressed per kg of body weight no differences for both extensor and flexor PT were found between national and international football players. There were no differences in the sprint times either. In the whole population, extensor peak torques were related to the 20-30-m sprint performance at 180, 240 and 300°/s (r = 0.77, r = 0.74, and r = 0.80, P < 0.01, respectively). High muscle strength was needed for 30-m sprint times. However, international football players were not stronger than national players, highlighting the major importance of both well-developed tactical sense and high technical standard.